Unprecedented reduction in births of very low birthweight (VLBW) and extremely low birthweight (ELBW) infants during the COVID-19 lockdown in Ireland: a 'natural experiment' allowing analysis of data from the prior two decades. Issue 9 (30th September 2020) - Philip, Roy K; Purtill, Helen; Reidy, Elizabeth; Daly, Mandy; Imcha, Mendinaro; McGrath, Deirdre; O'Connell, Nuala H; Dunne, Colum P
Abstract : Background: Aetiology of births involving very low birthweight (VLBW) and extremely low birthweight (ELBW) infants is heterogeneous and preventive strategies remain elusive. Socioenvironmental measures implemented as Ireland's response to the SARS-CoV-2 virus (COVID-19) pandemic represented a national lockdown, and have possibly influenced the health and well-being of pregnant women and unborn infants. Methods: Regional trends of VLBW and ELBW infants in one designated health area of Ireland over two decades were analysed. Poisson regression and rate ratio analyses with 95% CI were conducted. Regional data covering most of the lockdown period of 2020 were compared with historical regional and national data and forecasted national figures for 2020. Results: Poisson regression analysis found that the regional historical VLBW rate per 1000 live births for January to April, 2001–2019 was 8.18 (95% CI 7.21 to 9.29). During January to April 2020, an unusually low VLBW rate of just 2.17 per 1000 live births was observed, reflecting a rate ratio of 3.77 (95% CI 1.21 to 11.75), p=0.022, representing a 73% reduction of VLBW during the first 4 months of 2020 compared with same period for the preceding two decades. There were no ELBW infants admitted to the regional neonatal intensive care unit. National Irish VLBW rate for 2020 is forecasted to be reduced to approximate 400 per 60 000 births compared with the historical 500–600 range. Conclusion: An unprecedented reduction in regional births of VLBW and ELBW infants was observed in Ireland coinciding with the COVID-19 lockdown. Potential determinants of this unique temporal trend possibly reside in the summative socioenvironmental impact of the COVID-19 lockdown. Our findings, if mirrored in other regions that have adopted a lockdown, demonstrate the potential to evaluate these implicated behavioural and socioenvironmental modifiers to positively influence VLBW and ELBW rates globally.